Your turn : how to be an adult - Lythcott-Haims, Julie (Henry Holt and Company, 2021)
"Having tackled a far-reaching parenting crisis with her New York Times bestselling How to Raise an Adult, Lythcott-Haims is back with an equally powerful and persuasive book for the adult children of those hovering parents-and for everyone who struggles to be a grown-up in these challenging times"--